Case Report: Pericardial Effusion Treated With Pericardiectomy Plus Right Atrial Mass Resection: A 2-Year Follow-Up of Cardiac Rosai-Dorfman Disease - Conte, Edoardo; Brucato, Antonio; Petrella, Francesco; Passoni, Emanuela; Lauri, Gianfranco; Bigliardi, Mauro; Elisa, De Camilli; Ricciardi, Gabriella; Selmi, Carlo; Agostoni, Piergiuseppe; Alamanni, Francesco; Andreini, Daniele (Frontiers in Cardiovascular Medicine, 2021)
Background: Rosai-Dorfman disease (RDD) is rare a sinus histiocytosis typically causing lymphadenopathy. Heart involvement is anecdotal, and <30 cases of cardiac RDD (cRDD) have been reported so far. Case Presentation: A 46-year old woman with positive clinical history for RDD was admitted to our cardiology department with transthoracic echocardiography diagnosis of severe pericardial effusion and right atrial masses. Pericardiocentesis with catheter insertion was performed 3 days after the admission due to clinical evidence of cardiac tamponade. After 10 weeks of maximal medical therapy for inflammatory pericarditis, including non-steroidal anti-inflammatory drugs (NSAIDs), colchicine, steroids, and anakinra, at least 100 ml of pericardial citric liquid has been daily drained suggesting no clinical improvement. Pericardial liquid analysis demonstrated no malignant cells, but immunohistochemical analysis resulted positive for AE1–AE3, D2–40, S100, and CD68 consistent with an RDD diagnosis. Surgical management was judged clinically indicated, and 2 months after admission, the patient underwent pericardiectomy and debulking of atrial mass with freezing of remaining atrial neoformation. Regular clinical and echocardiography evaluation was performed without pericardial effusion recurrence after 2 years of follow-up. Conclusions: This is the first case ever reported of cRDD who survived after 2 years of follow-up. Pericardiectomy could be feasible and effective for recurrent pericardial effusion in cRDD. Close follow-up and a multidisciplinary environment is needed to take care of cRDD patients.